2020
DOI: 10.1590/0034-7167-2019-0423
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, anxiety and depression in patients with chronic obstructive pulmonary disease

Abstract: Objective: to assess quality of life, anxiety and depression in patients with Chronic Obstructive Pulmonary Disease. Method: a cross-sectional, quantitative study, conducted in a reference hospital for the treatment of pulmonary diseases. Seventy patients were assessed, using a sociodemographic and clinical questionnaire, Beck’s anxiety and Depression Inventories and the SF-36 Quality of Life Scale. Results: the participants had better quality of life in the vitality, mental health and social role functionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Anxiety and depression are the result of impaired QoL and inability to perform daily activities, di culties with personal care and dependence on family. 3,[14][15][16][17][18]67 We found that depression was associated with a lack of interest in daily activities and as a barrier to the practice of PA, corroborating with other studies. 6,27,67 All participants considered PA to be very important for well-being and improved QoL, expressing enthusiasm for the possibility for a program in the community designed for people with COPD.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Anxiety and depression are the result of impaired QoL and inability to perform daily activities, di culties with personal care and dependence on family. 3,[14][15][16][17][18]67 We found that depression was associated with a lack of interest in daily activities and as a barrier to the practice of PA, corroborating with other studies. 6,27,67 All participants considered PA to be very important for well-being and improved QoL, expressing enthusiasm for the possibility for a program in the community designed for people with COPD.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, there is a complex interaction between anxiety and dyspnoea. 13,14,18 Symptoms of anxiety and depression are often neglected and undertreated, 12,13,14,15,16,17,18,19,20,21 and further compounded by their relationship with tobacco smoking, the main cause of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained study results indicating higher anxiety level before FVB and lower QOL are not surprising. Some studies have already revealed that anxiety is related to a reduced QOL [18,[47][48][49], also taking into account QOL in particular age categories [48] and specific diseases [50][51][52]. Most of them proved that the presence of the somatic disease entity (e.g., SAS, COPD, asthma) and older age decrease QOL, especially physical health, psychological, and social QOL domains [50,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have already revealed that anxiety is related to a reduced QOL [18,[47][48][49], also taking into account QOL in particular age categories [48] and specific diseases [50][51][52]. Most of them proved that the presence of the somatic disease entity (e.g., SAS, COPD, asthma) and older age decrease QOL, especially physical health, psychological, and social QOL domains [50,52,53]. In our study, the patients with the better QOL perception and health perception felt less state and trait anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of supplemental elements into the COPD care bundle may also help optimize comprehensive patient care. For example, depression and anxiety are risk factors for COPD exacerbation and may have implications in COPD treatment compliance [13,14]. Screening for and treating these ailments may have utility in a COPD care bundle.…”
Section: Introductionmentioning
confidence: 99%